HSF1 promotes endometriosis development and glycolysis by up-regulating PFKFB3 expression - Yixin Wang; Jing Xiu; Tingting Yang; Chune Ren; Zhenhai Yu (BMC, 2021)
Abstract Background Endometriosis is a chronic hormonal inflammatory disease characterized by the presence of endometrial tissue outside the uterus. Endometriosis often causes infertility, which brings physical and mental pain to patients and their families. Methods We examined the functions of heat shock factor 1 (HSF1) in endometriosis development through cell count assay, cell-scratch assay and clone formation experiments. We used quantitative real-time PCR (qRT-PCR) and Western blot (WB) to detect HSF1 expression. Glucose and lactate levels were determined using a glucose (GO) assay kit and a lactate assay kit. Furthermore, we used a HSF1 inhibitor-KRIBB11 to establish a mouse model of endometriosis. Results Our data demonstrated that HSF1 promoted endometriosis development. Interestingly, HSF1 enhanced glycolysis via up-regulating PFKFB3 expression in endometriosis cells, which was a key glycolysis enzyme. Consistently, the HSF1 inhibitor KRIBB11 could abrogate endometriosis progression in vivo and in vitro. Conclusions Findings indicate that HSF1 plays an important role in endometriosis development, which might become a new target for the treatment of endometriosis. Electronic supplementary material Supplementary data are available.